Jeju Island Geopark - A Volcanic Wonder of Korea - Woo, Kyung Sik.; Sohn, Young Kwan.; Yoon, Seok Hoon.; Ahn, Ung San.; Spate, Andy.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book will deal with geological as well as cultural, historical, archaeological and biological aspects in Jeju Global Geopark. It will start with introduction of Jeju Global Geopark, geographic setting, habitats, history, economy and tourism, management, general geology and geosites, future geosites, other significant heritage sites, economically sustainable tourism, education and promotion and management plan.
Geographic Setting -- Habitats -- History -- Geology of Jeju Island -- Present Geosites- Sohn -- Future Geosites -- Other Heritage Sites -- Economy and Development of Sustainable Tourism -- Education and Promotion -- Management Plan.
Keywords: Geography; Geology; Regional planning; Nature Conservation; Earth Sciences; Geology; Landscape/Regional and Urban Planning; Nature Conservation